Consumer price knowledge in Turkey - Before and after the changeover of the national currency - KELEMCİ, GÜLPINAR (My University, 2006)
Purpose - The first objective of the paper is to determine whether the national currency changeover in Turkey has altered the level of consumer price knowledge. The second objective is to investigate the level of consumer price knowledge in an emerging economy, quite apart from the currency changeover. Design/methodology/approach - The paper looks at price knowledge by comparing consumers' price estimations with actual market prices. Data was collected, designed as a panel interview, at two points of time. The price data contains the actual prices of six selected products, from 27 retail stores in Istanbul. The choice of retail outlets was conducted in such a manner, that they provide a highly representative image of prices in Istanbul. The price estimation was obtained at personal interviews (599 individuals) outside a shopping situation in different parts of Istanbul. Findings - The analysis suggests that the price knowledge of Turkish consumers has not deteriorated since the currency changeover. On the contrary, it has slightly improved. According to the second objective, the price knowledge of consumers in an emerging economy turned out to be relatively poor, although the level of price differentiation is rather low in the market. Research limitations/implications - The first limitation is the context of price data, due to the specific economic infrastructure of an emerging country such as Turkey. The second limitation relates to the investigated product categories and refers to all of the results on the relatively poor price knowledge of Turkish consumers. Regarding further research, it would be useful to establish whether the price knowledge of Turkish consumers will improve in the future on account of the inflation rate, which has been declining noticeably during the past few months. In addition, other methods of measuring price knowledge can be used to determine whether the results for Turkish consumers are stable. Finally, including informal traders could raise the explanatory power of data about the price knowledge of Turkish consumers. Originality/value - Price knowledge in an emerging economy is poor. The effect of a currency changeover on price knowledge depends on the conversion arithmetic.
Keywords: Consumer behaviour; Consumers; Prices; Turkey